Mixed‐species associations in cuxiús (genus Chiropotes). Issue 5 (1st June 2015) - Shaffer, Christopher A.; Barnett, Adrian A.; Gregory, Tremaine; de Melo, Fabiano; Moreira, Leandro; Alvim, Thiago H. G.; Moura, Viviane S.; Filó, Anderson; Cardoso, Tatiane; Port‐Carvalho, Marcio; Santos, Ricardo Rodrigues dos; Boyle, Sarah A.
Abstract : Polyspecific or mixed‐species associations, where two or more species come together to forage and travel as a unit, have been reported in many primate species. These associations appear to offer a number of benefits to the species involved including increased foraging efficiency and decreased risk of predation. While several researchers have suggested that cuxiús (genus Chiropotes ) form mixed‐species associations, previous studies have not identified the circumstances under which cuxiús form associations or whether they form associations more often than would be expected by chance. Here we present data on the formation of mixed‐species associations by four species of cuxiús at eight different sites in Brazil, Suriname, and Guyana. We analyzed data from two of the study sites, (Biological Dynamics of Forest Fragments Project (BDFFP), Brazil and the Upper Essequibo Conservation Concession (UECC), Guyana, to assess whether associations occurred more than would be expected by chance encounters and identify the factors influencing their formation. Cuxiús showed a high degree of inter‐site variation in the frequency of time spent in association (ranging from 2 to 26% of observation time) and duration of associations (mean duration from 22 min to 2.5 hr). Sapajus apella was the most common association partner at most sites. At BDFFP, cuxiús formed associations more frequently but not for longer duration than expected by chance. For much of the year at UECC, associations were not more frequent or longer than chance. However, during the dry season, cuxiús formed associations with S. apella significantly more often and for longer duration than predicted by chance. Cuxiús at UECC formed associations significantly more often when in smaller subgroups and when foraging for insects, and alarm called significantly less frequently during associations. We suggest cuxiús form mixed‐species associations at some sites as an adaptive strategy to decrease predation risk and/or increase foraging efficiency. Am. J. Primatol. 78:583–597, 2016. © 2015 Wiley Periodicals, Inc.